Perceived nursing service quality in a tertiary care hospital, Maldives - Mariyam Nashrath (2018)
The present study explored nurses' and patients' expectations of nursing service quality, their perception of performance of nursing service quality performed by nurses, and compared nursing service quality, as perceived by nurses and patients. The sample consisted of 162 nurses and 383 patients from 11 inpatient wards/units in a tertiary care hospital in the Maldives. Data were collected using the Service Quality scale, and analyzed using descriptive statistics and the Mann-Whitney U-test. The results indicated that the highest expected dimension and perceived dimension for nursing service quality was Reliability. The Responsiveness dimension was the least expected dimension and the lowest performing dimension for nursing service quality as perceived by nurses and patients. There was a statistically significant difference between nursing service quality perceived by nurses and patients. The study results could be used by nurse administrators to develop strategies for improving nursing service quality so that nursing service delivery process can be formulated in such a way as to reduce differences of perception between nurses and patients regarding nursing service quality. © 2011 Blackwell Publishing Asia Pty Ltd..